An Effectiveness of Self-Management Education Through Self-Care and Quality of Life Resulting in Decreasing Readmission in Patients with Heart Failure: Based on Nursing Intervension: Systematic Review - Tery Luky Puspitawati; Ni Luh Widani (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction: The introduction of a research paper sets the stage by presenting the topic and context of the study. It aims to engage readers, provide background information, and outline the research problem or question. In this section, the researcher introduces the significance of the topic, discusses relevant literature, identifies gaps in existing knowledge, and states the research objectives. Objective: This research study aims to examine the impact of nurse-led self-care management educational programs on improving disease knowledge, self-care behavior and quality of life in heart failure patients. Method: This research is a systematic review that absolutely have many characteristics such as (author, year of publication, country, and number, age, and male percentage of patients in each group) and intervention parameters (type of intervention, ejection fraction at inclusion, form of proactive contact intervention, home visit status, time assessment, and status of educational strengthening). For instance, primary outcomes (rate of all-cause or HF-related readmission and all-cause mortality), quality of life evaluated by the Minnesota Living with Heart Failure Questionnaire (MLHFQ). Result: The results were showed that nurse-led interventions to be a cost effectiveness of treatment for heart failure patients, and nurses play an important role in educating and managing their condition. Overall, nurse-led self-care management education programs have demonstrated effectiveness in improving self-care and quality of life in heart failure patients. In concludes, Heart failure self-management education has been shown to improve patient self-care and quality of life. Implication: This research has maximum stakeholders that utilize evidence-based medicine to understand the role of nurses in the prognosis of HF patients to support and respect nurse-led educational efforts. The results of this study can provide strong evidence to expand the role of nurses and facilitate the planning and completion of nurse-led patient education programs. Conclusion: In concludes, it is also leads to significant improvements in quality of life. Due to nurse-led education programs that have been shown to reduce heart failure-related hospital readmissions and all-cause readmissions, as well as mortality rates in patients with heart failure.